THE USE OF MODERN GEODETIC TOOLS WHEN CREATING A GEODETIC BASE FOR SURVEYING LINEAR STRUCTURES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the necessary work on the preparation and updating of the topographic plan of the area where linear structures will be designed, as well as the method of tacheometric and leveling surveys. In order to conduct a large-scale survey in the fastest, most efficient and most promising way,it is necessary to evaluate the accuracy and performance of surveying instrumentation equipment.